HLA-G as a Tolerogenic Molecule in Transplantation and Pregnancy - Vera Rebmann; Fabiola da Silva Nardi; Bettina Wagner; Peter A. Horn (Journal of Immunology Research)
HLA-G is a nonclassical HLA class I molecule. In allogeneic situations such as pregnancy or allograft transplantation, the expression of HLA-G has been related to a better acceptance of the fetus or the allograft. Thus, it seems that HLA-G is crucially involved in mechanisms shaping an allogeneic immune response into tolerance. In this contribution we focus on (i) how HLA-G is involved in transplantation and human reproduction, (ii) how HLA-G is regulated by genetic and microenvironmental factors, and (iii) how HLA-G can offer novel perspectives with respect to therapy.